Baring Brothers & Co. records - Baring Brothers & Co.
Correspondence from Baring Brothers & Co. to the Bank of the United States and the U.S. Department of the Treasury. Also includes letter (22 May 1825) from Baring Brothers & Co. to LeRoy Bayard & Co (LeRoy, Bayard & McEvers), shipping firm of New York, N.Y.
London merchant bank founded in 1762 and reorganized in 1890 as Baring Brothers & Co. Ltd.
Collection material in English.
Keywords: United States. -- Department of the Treasury -- Correspondence; Bank of the United States (1816-1836) -- Correspondence; LeRoy, Bayard & McEvers (New York, N.Y.) -- Correspondence; Banks and banking -- England -- London; Banks and banking -- United States; Finance, Public -- United States; Shipping -- New York (State) -- New York